Perbandingan Nilai Efektivitas Kinerja Mesin Expeller Pressing Pada Proses Pergantian Screw Press Main Shaft - Nurlianna Tarigan (JURNAL VOKASI TEKNIK, 2023)
This research aims to compare the effectiveness of the Expeller Pressing machine performance before and after replacing the Screw Press Main Shaft and determine the magnitude of the increase in the percentage (%) of Crude Palm Kernel Oil (CPKO) oil after replacing the Screw Press Main Shaft, along with the use and service life of the machine. Expeller Pressing wear and tear and damage to machine components often occur, such as damage to the Screw Press Main Shaft which causes the effectiveness of machine performance to decrease. The decrease in the effectiveness of machine performance can be determined using the Overall Equipment Effectiveness (OEE) method. To increase the effectiveness of machine performance, improvements need to be made in the form of replacing the Screw Press Main Shaft. Based on the results of the discussion, the effectiveness of the Expeller Pressing machine performance before the Screw Press Main Shaft was replaced was 58% and after the replacement the machine performance effectiveness was 76%. Damage to the Screw Press Main Shaft also has an impact on the CPKO oil produced, before the replacement the percentage of oil obtained was 29.33% while after replacing the Screw Press Main Shaft the percentage of oil obtained was 44% so the percentage increase in oil after replacing the Screw Press Main Shaft is 14.67%.